The impact of gender, puberty, and pregnancy in patients with POLG disease. Issue 10 (18th September 2020) - Hikmat, Omar; Naess, Karin; Engvall, Martin; Klingenberg, Claus; Rasmussen, Magnhild; Tallaksen, Chantal M. E.; Samsonsen, Christian; Brodtkorb, Eylert; Ostergaard, Elsebet; de Coo, Rene; Pias‐Peleteiro, Leticia; Isohanni, Pirjo; et al.
Abstract: Objective: To study the impact of gender, puberty, and pregnancy on the expression of POLG disease, one of the most common mitochondrial diseases known. Methods: Clinical, laboratory, and genetic data were collected retrospectively from 155 patients with genetically confirmed POLG disease recruited from seven European countries. We used the available data to study the impact of gender, puberty, and pregnancy on disease onset and deterioration. Results: We found that disease onset early in life was common in both sexes but there was also a second peak in females around the time of puberty. Further, pregnancy had a negative impact with 10 of 14 women (71%) experiencing disease onset or deterioration during pregnancy. Interpretation: Gender clearly influences the expression of POLG disease. While onset very early in life was common in both males and females, puberty in females appeared associated both with disease onset and increased disease activity. Further, both disease onset and deterioration, including seizure aggravation and status epilepticus, appeared to be associated with pregnancy. Thus, whereas disease activity appears maximal early in life with no subsequent peaks in males, both menarche and pregnancy appear associated with disease onset or worsening in females. This suggests that hormonal changes may be a modulating factor.